Kenakalan Peserta Didik di Sekolah Dasar Islam Cokroaminoto 01 Kalabahi - Benyamin Mabilehi; Jeremia S. Wabang; Nur Fitra Manikita; Abdul Hamid Niwang; Zainal M. Sengadji (Politeknik Kampar, 2024)
Delinquency is the student’s conduct or actions that can lead to mismanagement, harm oneself or others, and breach both moral and social values. Delinquency occurs in all schools over time. The study was intended to know (1) what factors affected the delinquency of the student four class at Muhammadiyah Elementary School Islam cokroaminoto 01 kalabahi. (2) what are the forms of delinquency in the four class at Muhammadiyah Elementary School Islam cokroaminoto 01 kal;abahi. This type of research is qualitative work using a case study paradigm. The study was carried out in July- August 2020 at Muhammadiyah elementary school islam cokroaminoto 01 kalabahi. The object of this study was an four student delinquency at at Muhammadiyah Elementary School islam cokroaminoto 01 kalabahi. The data gathered in this study is a transcript of interviews, observation sheets, and documentation. The data analysis technique use miles and hubermen data collection, data presentation, data reduction, and withdrawal conclusions. Data validity tests were made using data triangulation techniques from different sources. Studies have shown that (1) delinquency that arises such as fights, bullying, and disobedience to school rules. Delinquency is not only due to oneself but also to family and surroundings. The influence of a family among them is a lack of attention from parent and family disharmony. Bad neighborhoods also have an effect on delinquency. (2) a student’s form of delinquency is that of uttering sentences in which he or she delebratery interferes with his students, causing class disturbances. Efforts by teachers and schools to deal with delinquency are (a) administering reproof, (b) administering punishment, (c) creating a student covenant letter. Such efforts are made to provide a lasting deterrent to further misbehavior. Preventing student behavior in the form of delinquency requires an evaluation of the school program as well as collaborative efforts between the school and the family.